Trends in Diarrhea Cases and Efforts to Control Them in South Sulawesi Province, Gowa Regency - Femy Febriyanti Masaid; Suryaningsi (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Diarrhea remains one of the major public health problems in Gowa Regency and has a substantial impact on morbidity among infants and toddlers. Despite various control efforts, the prevalence and trend of diarrhea cases have fluctuated over recent years, indicating persistent challenges in disease prevention and control. Objective: This study aims to describe the trend of diarrhea cases among infants and toddlers in Gowa Regency during the period 2016–2020 and to analyze factors influencing the observed trends. Methods: A descriptive quantitative study design was employed using secondary data obtained from the Gowa Regency Health Profile. The analyzed variables included the annual number of diarrhea cases and case detection targets, which were presented using tables and bar charts to illustrate temporal trends. Results: The results indicate fluctuations in the number of diarrhea cases, with the highest incidence recorded in 2017, followed by a substantial decline from 2018 to 2020. Preventive interventions, including improved access to sanitation facilities, hygiene promotion, and the free distribution of oral rehydration salts, appear to have contributed to the reduction in cases. However, program effectiveness was constrained by challenges such as limited availability of health personnel and the impact of the COVID-19 pandemic. Conclusion: The trend of diarrhea cases in Gowa Regency demonstrates an overall decline; however, achieving optimal and sustainable control requires a comprehensive, multidimensional approach supported by strong intersectoral collaboration.